Implications for functional diversity conservation of China’s marine fisheries - Zhao, Kangshun; He, Yuhan; Su, Guohuan; Xu, Congjun; Xu, Xiaoqi; Zhang, Min; Zhang, Peiyu (Frontiers in Marine Science, 2022)
Functional diversity is critical to ecosystem stability and resilience to disturbances as it supports the delivery of ecosystem services on which human societies rely. However, changes in functional diversity over space and time, as well as the importance of particular marine fish species to functional space are less known. Here, we reported a temporal change in the functional diversity of marine capture fisheries from all coastal provinces in China from 1989 to 2018. We suggested that both functional evenness (FEve) and functional divergence (FDiv) changed substantially over time, especially with considerable geographic variation in FEve in the detected patterns. Even within the same sea, the relative contribution of fishes with various water column positions and trophic levels in different waters have different patterns. Together these results underline the need of implementing specific climate-adaptive functional diversity conservation measures and sustainable fisheries management in different waters.